Development of PCR-based hybridization protocol for identification of streptococcal species. - Bentley, R W (1995)
16S rRNA of Streptococcus agalactiae, S. uberis, and S. parauberis was bound to streptavidin-coated magnetic beads by using a biotinylated oligonucleotide probe complementary to a highly conserved region of the molecule. In-solution hybridization of radiolabelled oligonucleotide probes to immobilized 16S rRNA allowed the specific identification of S. agalactiae and S. parauberis but not S. uberis. PCR was used to amplify a species-specific region of the 16S rRNA gene from these species. One of the PCR primers was biotinylated at the 5' end to allow purification of the amplified product on streptavidin-coated magnetic beads and subsequent denaturation to yield immobilized single-stranded DNA. Radiolabelled oligonucleotide probes were hybridized in solution to the single-stranded target molecule and enabled species-specific identification of the target organism. This protocol overcame problems associated with hybridization of the S. uberis-specific probe to 16S rRNA in solution. A similar procedure may enable the specific detection of other streptococci which exhibit a species-specific sequence in this region of the gene.